Pengaruh Mutu Layanan Perguruan Tinggi terhadap Kepuasan Mahasiswa (Studi pada Fakultas Ilmu Sosial Universitas Negeri Malang) - Setiawan, Eko Wahyu (Jurnal Ilmiah Administrasi Publik, 2021)
This study aims to examine the effect of higher education service quality on student satisfaction. The variables used in this study are service quality and student satisfaction. The research applies the SERVQUAL theory by Abdullah (2006). The data collection technique used is by using a questionnaire with 343 respondents from the Faculty of Social Sciences (FIS) UM. FIS was chosen because it was declared as the most stable faculty in academic administration affairs (Renstra FIS UM, 2015-2019). From the results of this study, the coefficient of determination R Square shows a value of 0.482 or 48.2%. This means that the Student Satisfaction variable (Y) is influenced by 48.2% by Reliability (X1), Responsiveness (X2), Assurance (X3), Empathy (X4), and Tangibles (X5) while the remaining 51.8% is influenced by other variables outside the five variables. which were investigated in this study. While the most significant indicator on the Service Quality variable is Empathy with a regression coefficient of 0.307. This shows that the attention of the Academic Administration given to individual students is quite high and has a significant effect on student satisfaction.